PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN STRATEGI PROBLEM BASED LEARNING DI KELAS IV SD NEGERI 12 MUNDAM SAKTI KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG - Randi Eka Putra (LPPM Universitas Muhammadiyah Muara Bungo, 2019)
This study began with a problem that occurred in Class IV SD 12 Mundam Sakti, namely the low activity and student learning outcomes. This can be seen from the results of observation and analysis of the results of UH I students. This study aims to reveal the effect of Problem Based Learning (PBL) strategies on thematic learning activities and outcomes that are specific to mathematics learning. The subjects of the study were the fourth grade students of SDN 12 Mundam Sakti District IV Nagari, Sijunjung Regency, totaling 20 people.This research is a classroom action research with a simple qualitative and quantitative approach. In its implementation, this study consisted of two cycles conducted by researchers. Each cycle consists of planning activities, implementing actions accompanied by observations and reflections in each cycle. This research was conducted in the first semester of the 2014/2015 school year at SDN 12 Sakti District IV Nagari, Sijunjung Regency. The research data was collected through observations, field notes, videos, documentation and test results. The results of the analysis of the research data indicate that the use of PBL strategies can increase the activities and learning outcomes of Mathematics in class IV SDN 12 Sakti District IV Nagari Sijunjung Regency. This can be seen from oral activity, writing, and mental, has increased from cycle I to cycle II. The same thing is seen in student learning outcomes, namely: (1) the average student learning outcomes in cycle I 73.5 and in cycle II to 87.5. Seeing the results of this study, the classroom action research in the use of PBL strategies in mathematics learning needs to be applied and developed in order to improve the quality of education in the future.